Analysis of Parameters of Sintered Metal Components Created by ADAM and SLM Technologies - Timko, Pavol; Czanova, Tatiana; Czan, Andrej; Slabejova, Silvia; Holubjak, Jozef; Cedzo, Miroslav (Manufacturing Technology Journal, 2022)
Atomic Diffusion Additive Manufacturing (ADAM) is a recent metal sintering process based on known composite printing technology. ADAM can be classified as indirect additive production using fibre of metal powder bound in a plastic matrix. The plastic binder allows the metal powder to remain in place when is printing. Thus, a "green part" is printed and then the plastic binder is removed by the post-washing and sintering process. The aim of this work is providing a brief description of the ADAM process patented by Markforged. Furthermore, the main task was to compare the technology with other sintering technology, namely SLM technology. It works on the basis of selective bonding of metal powder using the thermal energy of the laser beam. Parameters, such as dimensional and shape accuracy, roughness of printed surfaces or tensile strength of printed samples were examined and compared. Dimensional accuracy of the ADAM process was evaluated using ISO IT grades - determined on the basis of the reference standard. The observed accuracy of the sintering process was comparable to traditional production processes.
Keywords: Additive Production; Markforged; Sintering; SLM; 17-4 PH; 316L-0407; Roughness